Impaired coronary and myocardial flow in severe aortic stenosis is associated with increased apoptosis: a transthoracic Doppler and myocardial contrast echocardiography study. Issue 2 (20th May 2005) - Galiuto, L; Lotrionte, M; Crea, F; Anselmi, A; Biondi-Zoccai, G G L; De Giorgio, F; Baldi, A; Baldi, F; Possati, G; Gaudino, M; Vetrovec, G W; Abbate, A
Abstract : Objective: To test the hypothesis that impaired coronary and myocardial blood flow are linked with increased myocyte apoptosis, thus establishing a link between pressure overload and left ventricular (LV) remodelling. Methods and results: Peak diastolic coronary blood flow velocity (CBFV) was evaluated at transthoracic Doppler echocardiography, and signal intensity (SI) and the rate of SI rise (β) were measured at myocardial contrast echocardiography in 11 patients with severe aortic stenosis and LV hypertrophy. In the same patients, biopsies were obtained from the anterolateral LV free wall during surgery and analysed for cardiomyocyte apoptosis. LV mass corrected CBFV (CBFVI) was significantly lower in patients than in controls (median 0.100 cm·g/s (interquartile range 0.07–0.115) v 0.130 cm·g/s (0.130–0.160), p = 0.002). Similarly, SI*β was significantly lower in patients than in controls (11 1/s (8–66) v 83 1/s (73–95), p = 0.001). Apoptotic rate was increased in aortic stenosis more than 100-fold versus controls (1.2% (0.8–1.4) v 0.01% (0.01–0.01), p < 0.001) and inversely correlated with lower CBFVI and SI*β ( r = −0.77, p = 0.001 for both). Conclusions: Patients with severe aortic stenosis and LV hypertrophy have impaired myocardial perfusion, which is associated with enhanced cardiomyocyte apoptosis. Impaired myocardial perfusion and the ensuing oxygen demand–supply imbalance may, at least partially, be responsible for increased apoptosis and possible transition to heart failure, thus establishing a link between pressure overload, LV remodelling, and heart failure.